1995
DOI: 10.1111/j.1600-0773.1995.tb01042.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cholecystokinin Receptor Agonist and Antagonists on Morphine Dependence in Mice

Abstract: In the present study, the effect of cholecystokinin agonists and antagonists on dependence to morphine in mice has been investigated. Mice were treated subcutaneously with morphine (50, 50 and 75 mg/kg) three times daily for 2-4 days, and a last dose of morphine (50 mg/kg) was administered on day 3, 4 or 5. Withdrawal syndrome (jumping) was precipitated by naloxone (2.5, 5 and 10 mg/kg) which was administered intraperitoneally 2 hr after the last dose of morphine. To study the effects of cholecystokinin recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
(38 reference statements)
1
10
0
Order By: Relevance
“…This effect also appears to be mediated by CCK A receptors. Data from in vivo studies have shown that both CCK agonists and antagonists reduce naloxone‐precipitated withdrawal signs in morphine‐dependent mice ( Zarrindast et al ., 1995 ). Similar conflicting results come also from antinociception studies (reviewed by Cesselin, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect also appears to be mediated by CCK A receptors. Data from in vivo studies have shown that both CCK agonists and antagonists reduce naloxone‐precipitated withdrawal signs in morphine‐dependent mice ( Zarrindast et al ., 1995 ). Similar conflicting results come also from antinociception studies (reviewed by Cesselin, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier evidence that daily administration of CCK antagonists left the withdrawal syndrome in morphine‐dependent animals unaffected ( Dourish et al ., 1988 ; Panerai et al ., 1987 ; Xu et al ., 1992 ) and that CCK agonists did not precipitate a withdrawal syndrome in dependent animals ( Maldonado et al ., 1994 ; Pournaghash & Riley, 1991 ) suggested that the development or expression of physical dependence did not involve CCK systems. However, later works showed that CCK agonists reduced or prevented the withdrawal signs precipitated by naloxone in morphine‐dependent mice ( Zarrindast et al ., 1995 ; Rezayat et al ., 1997 ). On the other hand, a CCK B receptor antagonist potentiated the inhibition of morphine withdrawal of an inhibitor of enkephalin catabolism ( Maldonado et al ., 1995 ).…”
Section: Introductionmentioning
confidence: 99%
“…On day 4, a single dose of morphine (50 mg/kg) was injected 2 h before naloxone treatment. Each mouse received ten doses of morphine (Hosseinzadeh and Lary, 2000;Zarrindast et al , 1995).…”
Section: Preliminary Chemical Testsmentioning
confidence: 99%
“…After the naloxone challenge, mice were immediately placed in a glass cylinder (30 cm high, 20 cm in diameter). The number of jumps was recorded for 30 min after naloxone (NXL) injection (Hosseinzadeh and Lary, 2000;Zarrindast et al , 1995).…”
Section: Preliminary Chemical Testsmentioning
confidence: 99%
“…All the drugs were administered subcutaneously. The doses of the drugs were based on previous studies (Dourish et al 1988;Rezayat et al 1994;Zarrindast et al 1995Zarrindast et al & 1997.…”
Section: Methodsmentioning
confidence: 99%